2011
DOI: 10.4067/s0717-92002011000200005
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicación in vitro de Eucalyptus globulus mediante sistema de inmersión temporal

Abstract: SUMMARYWith the object of establishing mass production methods of Eucalyptus globulus, factors affecting its in vitro multiplication stage by temporary immersion were studied. For this, five microshoots per flask containing 250 mL of Murashige and Skoog medium were disposed. Factors such as immersion frequency (6, 12, 24, 48 h), immersion time (1, 2 and 3 min) and macronutrients concentration (25, 50 and 100 %) were studied. In a second stage, the addition into medium of 6-bencylaminopurine (0, 2.2 and 4.4 µM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
(13 reference statements)
2
5
0
Order By: Relevance
“…We found that the long immersion frequency (12 h) have better result than short immersion frequency (3h). The similar result also shown in in vitro multiplication of Eucalyptus globulus , which was obtained the best multiplication in immersion time 2 min and immersion frequency 12 h [48].…”
Section: Resultssupporting
confidence: 82%
“…We found that the long immersion frequency (12 h) have better result than short immersion frequency (3h). The similar result also shown in in vitro multiplication of Eucalyptus globulus , which was obtained the best multiplication in immersion time 2 min and immersion frequency 12 h [48].…”
Section: Resultssupporting
confidence: 82%
“…The frequency and the immersion time are the main factors that influence the proliferation and hyperhydration of shoots, and this physiological disorder can occur by the formation of an aqueous film around the tissues that may interfere with gas exchanges between the outer tissue and the cell surface, since gas diffusion rates are about 10.000 times slower in water than in air (González et al, 2011;Jackson, 2003), a fact that corroborates the results of Chakrabarty et al (2003), reported above.…”
Section: Discussionsupporting
confidence: 83%
“…In Tectona grandis L. it was observed the presence of hyperhydric shoots in the highest concentration of BA used (6.6 μM), which impaired shoots proliferation in TIS (Quiala et al, 2012). In E. globulus, the highest percentage of hyperhydration (61.9%) occurred in the treatment with 4.4 uM BA when compared to treatments with 2.2 (51,4%) and without BA (45,3%) (González et al, 2011). In addition to higher concentration of cytokinins in culture medium, it should be taken into account that prolonged exposure times to BA can also lead to a physiological depletion of the material, thus reducing the rate of shoot proliferation in successive subcultures.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…When the frequency is reduced to 1 immersion/48 h, all these parameters decrease. In Eucalyptus globulus, González et al (2011), also showed that this immersion frequency (1 immersion/48 h) significantly decreased the multiplication rates, which was due to a reduction in the supply of nutrients.…”
Section: Shoot Numbermentioning
confidence: 84%